Rhizobia Inoculants for Alfalfa in Acid Soils: A Proposal for Uruguay - Tabares-da Rosa, Sofía (2019)
Ensifer meliloti establishes symbiosis with Medicago sativa (alfalfa) and other perennial species of Medicago that grow in soils with neutral to alkaline pH, whereas Ensifer medicae makes symbiosis with annual medics adapted to moderately acid soils. The new species Rhizobium favelukesii, whose strain is LPU83, belongs to an alfalfa group of inefficient rhizobia, known as the Oregon type, initially represented by Rhizobium sp. strain Or191. R. favelukesii is considered a potential risk in the acid soils where alfalfa is grown, and could explain the inefficient nodulation observed in different countries. In acidic soils from the «Dairy Basin» of Uruguay, producers inoculate alfalfa with E. melliloti U143 strain. This edaphic condition is often marginal because the maximum potential of rhizobia-alfalfa symbiosis is not achieved at acid pH. Although Uruguay has an outstanding position in the production and use of rhizobial inoculants, the commercial strains currently used in Trifolium, Lotus and alfalfa were selected about 50 years ago in different conditions that the present ones as a consequence of: i) the displacement of cultivated pastures to other sites, ii) the sowing method, and iii) the use of new cultivars. In this review, alfalfa inoculation is analyzed in some countries and a strategy for the development of an inoculant suitable for Uruguayan acid soils is proposed. This strategy is based on the selection of efficient and competitive strains, as the first selection criteria, and persistency in soil as the second one.